2013
DOI: 10.1080/07294360.2013.806442
|View full text |Cite
|
Sign up to set email alerts
|

Persist or withdraw: the importance of external factors in students' departure intentions

Abstract: The role of institutional factors in students' intentions to persist with or withdraw from their studies is well established in the literature. More recently, the influence of factors external to the institution has been highlighted as well. This study investigates the relationship between levels of engagement of first-year students undertaking a core business subject at a large university in Australia and their departure intentions. It was found that their propensity to persist was positively associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…With governments aiming for greater access to higher education, while simultaneously requiring increased retention and completion, universities have to explore ways in which to ease transition and enhance first-year experience. Even though there are external factors beyond the control of universities (Leveson et al 2013), they can take steps to create an environment in which students' chances of persisting increase. For instance, researchers have stressed that being part of a community is important for students to do well at university-this concerns both academic and social integration (e.g.…”
Section: Transition and First-year Experiencementioning
confidence: 99%
“…With governments aiming for greater access to higher education, while simultaneously requiring increased retention and completion, universities have to explore ways in which to ease transition and enhance first-year experience. Even though there are external factors beyond the control of universities (Leveson et al 2013), they can take steps to create an environment in which students' chances of persisting increase. For instance, researchers have stressed that being part of a community is important for students to do well at university-this concerns both academic and social integration (e.g.…”
Section: Transition and First-year Experiencementioning
confidence: 99%
“…Hence, Hovdhaugen [52] links the level of student effort with the probability of transfer or dropout. Moreover, there is an interconnection between external and internal factors that lead to late dropout, making it difficult to isolate these factors [53]. Therefore, this group of educational trajectories should be studied in more detail, considering the behavior in courses of lower failure rate and also surveying the satisfaction level and the alternatives that are being considered over time, according to the Investment model [33].…”
Section: Discussionmentioning
confidence: 99%
“…Tinto (1975) argued that academic and social integration are important factors against student attrition at university. Moreover, studies by Johnson (2008), Hoffman et al (2002), Willcoxson et al (2011) and Leveson et al, (2013) revealed that aside from academic and social integration, attrition has also been shown to be linked to prior academic performance, engagement with faculty and students, financial problem and lack of commitment to study. Willcoxson et al (2011) also noted that attrition in the first year of study could result from different reasons as compared to attrition in later years of study.…”
Section: Introductionmentioning
confidence: 99%